Improving Skills of Writing Observation Report Texts Using Project-Based Learning (PjBL) Method in Grade X Students of SMA Negeri 1 Jangka Buya Pidie Jaya - Ira Munira; Nurlaili; Rahmi, Hayatun (Yayasan Sagita Akademia Maju, 2025)
This study entitled